PERBEDAAN PENGARUH EKSTRAK MENTIMUN DAN AIR JAHE TERHADAP TEKANAN DARAH LANSIA DENGAN HIPERTENSI - Yuliantari, Ni Wayan (Coping: Community of Publishing in Nursing, 2015)
Hypertension is a condition which blood pressure ?140/90 mmHg and more common in the elderly because of increased peripheral vascular resistance. This can be overcome by taking cucumber extract or ginger water. This study aimed to assess the effect of differences in cucumber extract and ginger water on blood pressure of elderly with hypertension conducted in Puskesmas II Denpasar Barat, on May 5 until 18, 2014. This research is quasy experimental design. There are 30 elderly were selected by purposive sampling. Previously performed a pre-test measurement of blood pressure in each group. In the first group was given cucumber extract from 100 grams of cucumber and the second group was given a dose of ginger with 4 gr/200 cc of water given for 2 weeks every morning before breakfast. Post-test performed 4 times for 2 weeks. Data collection was conducted using observation sheets measuring blood pressure. Results of Mann-Whitney test was found level of systolic and diastolic blood pressure is p= 0.114 and p= 0.959 (p value ?0.05), which means there is no difference in systolic blood pressure between the groups of elderly with hypertension were given cucumber extract and ginger water along with there is no difference in diastolic blood pressure between the groups of elderly with hypertension were given cucumber extract and ginger water.
Keywords: Blood Pressure; Cucumber Extract; Ginger Water